EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN ASSESSMENT FOR LEARNING (AfL) MELALUI PENILAIAN TEMAN SEJAWAT PADA MATERI PERSAMAAN GARIS DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA SISWA MTsN DI KABUPATEN SRAGEN - Sholeh Muntasyir; Budiyono Budiyono; Budi Usodo (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research is aimed to view: (1) which gives a better learning achievement,  learning Numbered Head Together (NHT) with the AfL through peer assessment, NHT or direct learning, (2) which gives better achievement, low, medium or high level creativity in mathematics learning, (3) which has better mathematics learning achievement, student having low, medium or high learning creativity on each learning model, (4) which learning model gives better achievement in learning mathematics, learning model Numbered Head Together (NHT) with the AfL through peer assessment, learning models Numbered Head Together (NHT) or direct learning model on each student’s creativity level. This research was a quasi-experimental research with 3x3 factorial design. The study population was all students MTsN in Sragen. The sampling technique used a stratified cluster random sampling. The samples were 294 students, consisted of 95 students in the first experimental class, 100 students in the second experimental class and 99 students in the control class. Data collected through mathematics achievement tests and questionnaires of study mathematics creativity. Hypothesis testing used two- way analysis of variance with unbalanced cells. The results show as follows. (1) The NHT with the AfL through peer assessment model provide a better learning performance than the NHT and direct learning model. The NHT model provide a better learning performance than the direct learning model. (2) Students with a high level learning creativity have a better achievement than students who have medium and low creativity. Students with medium and low level creativity gain the same learning achievement. (3) In the NHT learning model with the AfL through peer assessment, students with a high level creativity gain better learning achievement than students with medium learning creativity, but when compared with students who have low learning creativity get the same academic achievement. While using NHT  model and direct learning, students with high, medium and low creativity get the same learning achievement. (4) At the high level of creativity,  NHT with the AfL through peer assessment model gived a better performance than the NHT and direct learning, NHT and direct learning models provide the same learning performance. Students having medium and low level of creativity provide the same learning achievement in each learning models.Keywords : NHT, AfL, peer assessment,  creativity in learning.